The Culture and Civilization of Pakistan - Kishwer Naheed (Karachi Oxford University Press, 2017)
In this book, the preeminent poet and author Kishwar Naheed presents a fascinating account of Pakistan's rich and varied cultural landscape.
Keywords: Pakistan -- Civilization